Advances in Social Media Analysis - Gaber, Mohamed Medhat; Cocea, Mihaela; Wiratunga, Nirmalie; Goker, Ayse (Studies in Computational Intelligence, 2015)
This volume presents a collection of carefully selected contributions in the area of social media analysis. Each chapter opens up a number of research directions that have the potential to be taken on further in this rapidly growing area of research. The chapters are diverse enough to serve a number of directions of research with Sentiment Analysis as the dominant topic in the book. The authors have provided a broad range of research achievements from multimodal sentiment identification to emotion detection in a Chinese microblogging website. The book will be useful to research students, academics and practitioners in the area of social media analysis.  .